SUFISM AND ECONOMIC RESILIENCE: TRAJECTORY OF TAREKAT NAQSYABANDIYAH-KHALIDIYAH BABUSSALAM (TNKB) - Ziaulhaq Hidayat (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2022)
This article provides updated information on the tarekat following the entrepreneurial bankruptcy in the Tarekat Naqsybandiyah-Khalidiyah Babussalam (TNKB). This study charts the TNKB trend regarding the spiritual institution’s economic toughness. This research asks how TNKB will be able to continue operating if its founder no again walks away from entrepreneurs and what other economies may emerge in his place. Findings from the study show that the entrepreneurial bankruptcy of TNKB entrepreneurs is strongly tied to the conflict of the leader, which is exacerbated by Tuan Guru’s need to concentrate on other issues. Uang salam originated as a substitute for a new economic source to preserve the TNKB. Uang salam is a practice that persists until it eventually makes room for commodification. Commodification is a tactic used by TNKB as part of its survival plan after the entrepreneurial bankruptcy so that it can continue to exist and advance up to the present.